Tumor Budding as a Marker for Poor Prognosis and Epithelial–Mesenchymal Transition in Lung Cancer: A Systematic Review and Meta-Analysis - Thakur, Nishant; Ailia, Muhammad Joan; Chong, Yosep; Shin, Ok Ran; Yim, Kwangil (Frontiers in Oncology, 2022)
Introduction: Currently, tumor budding (TB) is considered to predict the prognosis of patients. The prognostic significance of TB has also been explored in patients with lung cancer, but has not been fully clarified. In the present meta-analysis, we evaluated the prognostic significance, clinicopathological value, and relationship with epithelial-mesenchymal transition (EMT) of TB in lung cancer. Methods: The MEDLINE, EMBASE, and Cochrane databases were searched up to July 7, 2021, for the relevant articles that showed the relationship between TB and prognosis in patients with lung cancer. For statistical analysis, we used pooled hazard ratios (HRs) with their corresponding 95% confidence intervals (CIs) to assess the correlation between high-grade TB expression and overall survival (OS), disease-free survival (DFS), progression-free survival (PFS), clinicopathological factors, and EMT markers. Results: A total of 3,784 patients from 10 independent studies were included in the statistical analysis. Our results indicated that high-grade TB was significantly associated with poor OS (HR 1.64 (95% CI, 1.43-1.87), and DFS (HR 1.65 (95% CI, 1.22-2.25). In terms of clinicopathological characteristics, high-grade TB was associated with larger tumor size, higher T and N stage, pleural invasion, vascular invasion, lymphatic invasion, severe nuclear atypia. Interestingly, smoking showed significant association with high grade TB, despite of previous studies could not showed significant relationship between them. Furthermore, through our systematic analysis, high-grade TB showed a significant relationship with EMT markers. Conclusion: Our findings indicate that high-grade TB is associated with a worse prognosis in patients with lung cancer. TB evaluation should be implemented in routine pathological diagnosis, which may guide the patient’s treatment.